Professional development in classroom discussion to improve argumentation: Teacher and student outcomes. (June 2023) - Wilkinson, Ian A.G.; Reznitskaya, Alina; D'Agostino, Jerome V.
Abstract: The purpose of this study was to examine the effects of a year-long professional development program in classroom discussion designed to improve students' argumentation skills in language arts classes. Twenty-six fifth-grade teachers and their 471 students at two research sites participated: 14 teachers in the experimental condition, who received the professional development, and 12 teachers in the comparison condition. Results showed that the professional development led to statistically significant improvements in the quality of teachers' facilitation and student argumentation during discussions, and in students' performance on individual argumentative reading and writing tasks following the discussions, at the end of the year. Findings suggest that the professional development for teachers resulted in strengthened student abilities to connect positions with relevant reasons and evidence, and that argumentation skills acquired in the discussions may have transferred to students' individual argumentation, at least for reading outcomes. Highlights: Discussion about text provides an ideal context to support argumentation. Facilitating such discussions presents a serious challenge for teachers. Few studies have targeted PD in argumentation in language arts classes. PD strengthened student abilities to connect positions with reasons and evidence. Argumentation in discussions likely mediated some individual student outcomes.